The effect of first nocturnal ejaculation timing on risk and sexual behaviors of Korean male adolescents - Mi-Ji Lee; Go-Eun Yang; Hee Won Chueh; Jae Hong Park; Jae-Ho Yoo (Korean Society of Pediatric Endocrinology, 2017)
PurposeThis study evaluated the effect of first nocturnal ejaculation timing on risk and sexual behaviors of Korean male adolescents.MethodsWe analyzed data from the 10th edition of the Korea Youth Risk Behavior Web-based survey that was conducted with male high school adolescents in grades 10-12. The survey included 17,907 adolescents, and 10,326 responded their experience of first nocturnal ejaculation. Of these, 595 had their first nocturnal ejaculation in ≤grade 4 ("early puberty") and 9,731 had their first nocturnal ejaculation in ≥grade 5 ("normal puberty"). We analyzed differences between these 2 groups in risk and sexual behaviors.ResultsEarly first nocturnal ejaculation showed a positive association with sexual intercourse (odds ratio [OR], 3.27; 95% confidence interval [CI], 2.56-4.17), sexual debut at elementary school age (OR, 7.45; 95% CI, 5.00-11.10), and having had a sexually transmitted disease (OR, 6.60; 95% CI, 3.94-11.08). After a multiple logistic regression to adjust for socio-demographic variables, early first nocturnal ejaculation was still positively associated with sexual intercourse (OR, 2.73; 95% CI, 2.03-3.69), sexual debut at elementary school age (OR, 5.96; 95% CI, 3.47-10.22), and having had a sexually transmitted disease (OR, 5.17; 95% CI, 2.52-10.20). Early first nocturnal ejaculation was positively associated with alcohol consumption, smoking, and substance use. However, this was not statistically significant after adjusting for several socio-demographic variables.ConclusionThere is a positive association between early nocturnal ejaculation and sexual behaviors in male adolescents. Proactive education about sexual behaviors is required for adolescents who reach sexual maturity early.